(+x)+x=(x-2)=2x+33x+9=*(x+5)=1002(X+X+)=+x=6x3200=450+5X+XX-=612x-8x=*2X==+=-=+=—8=1618(x-2)=27012x=300-4x7x+==+25=>8-2x=66x-=-3x=1703(x+)=+8=436x-3x=18x+3x=703(x+3)==-^=909x-40=5x-^5+9=2148-27+5x=+x+2仁56x+2x+18=78(200-x)弋=30(x-140)-^70=42x-97=-48=(-)*44(x-)=-=-9x=(-)*46x+=+25x=134x+=+3x=(x+)==-x=-20=43x+6=182(x-3)=+7=*(+x)=+4*=915x+=(x-3)吃=+=1345(x+8)=+9x=+=51x+3x+10=703(x+3)=50-x+35x+15=-5x=23x=x+100x+=+18=483(x+)=-43x=-45=-==2x=56X-=-2X=183X+=>2=+=2x+>6—16X).2=—X===14x+14x+14x=653—5x=+6x=—=-14x=14x+7x=89x-3x=66x-8=45x+x=9x-8=6x4/5x=202x-6=127x+7=146x-6=05x+6=112x-8=101/2x-8=424x+x=506/7x-8=43x-8=306x+6=123x-3=15x-3x=42x+16=195x+8=1914-6x=815+6x=275-8x=44+5x=910-x=84x-18=135x+9=-6x=—=+9=176-2x=119+4x=409+6x=14x+9x=4+72x+9=178-4x=66x-7=127x-9=8x-56=18-7x=1x-30=126x-21=216x-3=6x+4+8=237x-12=8X-=-2X==>2=>.5=>6—16X).2=—X===—+=—=—4x=201/3x+5/6x=+34x=118x—14x=1223x—5X4=1412+34x=5622—14x=124X+10==903x—8=163x+9=+7x=-5=-=612x+8x=(x-2)=494X8+2x=36(x-2)-3=7x宁5+9=21(200-x)-5=3048-27+5x=31X-=-3X=68320=45+6XX-=8x+=—2x=15X+==303x+9=367(x-2)=73x+9=1218(x-2)=2712x=320++x=-3x=530-x=+2x=6420-3x=1703(x+5)=+9=406x+3x=+6=3x5X3-x=840-8x=5x-5=2148-20+5x=31x+2x+8=80200-x-5=3070宁x=-3x=
300道解方程题 来自淘豆网m.daumloan.com转载请标明出处.